The development of Christology during the first hundred years, and other essays on early Christian Christolog y - Talbert, Charles H. (Novum Testamentum, Supplements, 2011)
Entering the debate about the development of Christology among Jesus' earliest followers, this volume critiques both the traditional evolutionary view that posited an elementary early Jewish Christology that developed in complexity as it was increasingly Hellenized and the more recent attempt to see a full-orbed Christology both as early and as Jewish, not Hellenistic, in its categories. It contends that during the first 100 years Jesus' followers employed four models from their milieu, Jewish and Greco-Roman, both to understand and to communicate their Christologies. These models were appropriated because they were appropriate vehicles for expressing the impact of Jesus on them, past, present, and future.